2001
DOI: 10.1614/0043-1745(2001)049[0668:eeocaf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on CGA-248757 and flumiclorac efficacy/soybean tolerance

Abstract: The effect temperature, light intensity, time to initial light exposure, relative humidity, and the presence of dew have on CGA-248757 and flumiclorac efficacy was evaluated in laboratory trials. Increasing temperature from 10 to 40 C increased CGA-248757 and flumiclorac activity on common lambsquarters by 79 and 87%, respectively. Similarly, increasing temperature from 10 to 40 C increased CGA-248757 and flumiclorac activity on redroot pigweed by 68 and 60%, respectively. Increasing light intensity from 0 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 15 publications
1
39
1
2
Order By: Relevance
“…Moreover, this study showed greater biomass reduction under warm conditions for the mixtures 2.4-D+dicamba and 2.4-D+florasu-lam. These results are in agreement with the previous reports describing higher herbicide activity under high temperature conditions compared to low temperature [5,16,17]. In contrast to temperature, relative humidity did not influence weed response to herbicide stress.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, this study showed greater biomass reduction under warm conditions for the mixtures 2.4-D+dicamba and 2.4-D+florasu-lam. These results are in agreement with the previous reports describing higher herbicide activity under high temperature conditions compared to low temperature [5,16,17]. In contrast to temperature, relative humidity did not influence weed response to herbicide stress.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to temperature, relative humidity did not influence weed response to herbicide stress. Similar results were reported by F a u s e y and R e n n e r [17], but generally this finding is inconsistent with most of the previous papers that have proven a weaker response of weeds to herbicides at low relative humidity [4,18,19]. The lack of differences in weed response proved in this research may be due to the small differences between the relative humidity levels tested.…”
Section: Discussioncontrasting
confidence: 63%
“…Na última avaliação, aos 35 DAA, o volume de orvalho de 500 mL m -2 apresentou o melhor controle, atingindo 30%. Esse baixo controle foi provavelmente devido à perda do glyphosate por escorrimento, concordando com Fausey & Renner (2001).…”
Section: Resultsunclassified
“…High temperatures favor the activity of PROTOX inhibitors (Li et al, 2000;Fausey & Renner, 2001;Price et al, 2004;HattermanValenti et al, 2011. ) For example, in experiments using flumiclorac and fluthiacet, it was found that a temperature rise from 10 o C to 40 o C increased weed control under greenhouse conditions.…”
Section: Temperaturementioning
confidence: 99%